Designing a Biogas Plant for an Educational and Scientific Livestock Complex - Miroshnichenko, Irina V.; Nikulina, Nadiia V. (KnE Life Sciences, 2022)
To design biogas plants, it is necessary to have accurate data about the properties and biogas productivity of the available substrates. Reference data should not be used because the performance of the same substrate can vary significantly. In this research,chicken, horse, sheep and rabbit manure from one of the farms inthe Belgorod region of Russia were analyzed, and the parameters of a biogas station for the processing of this raw material were calculated.The biogas yield of the substrates was determined using the Hohenheim Biogas Yield Test. It was found that the specific biogas yield from the droppings of broilers, laying hens, rabbits, sheep, and horses, and from corn silage were, respectively, 456, 363, 390, 189, 116 and 618 ml/g оDM. The methane content in the biogas was 58.00, 58.50, 57.00, 62.00, 65.00 and 53.60%, respectively. In most cases, the obtained results differed significantly from the data presented in publications of other researchers and reference books.The biogas plant parameter calculations were made according to generally accepted equations, taking into account the characteristics of the studied substrates. Based on the results, it can be concluded that to dispose of the animal excrement of this farm, it is necessary to build a biogas plant with a bioreactor of volume 102.2 m3 and an engine with a power of 12 to 31 kW. The planned output of electric and thermal energy would be 246.19 and 410.27 kWh/day, respectively. Keywords: Hohenheim Biogas Yield Test, rabbit manure, horse dung, sheep manure, chicken droppings, biogas yield of substrates